ATR phosphorylates SMARCAL1 to prevent replication fork collapse - Couch, Frank B; Bansbach, Carol E; Driscoll, Robert; Luzwick, Jessica W; Glick, Gloria G; Bétous, Rémy; Carroll, Clinton M; Jung, Sung Yun; Qin, Jun; Cimprich, Karlene A; Cortez, David (Genes & development, 2013)
The DNA damage response kinase ataxia telangiectasia and Rad3-related (ATR) coordinates much of the cellular response to replication stress. The exact mechanisms by which ATR regulates DNA synthesis in conditions of replication stress are largely unknown, but this activity is critical for the viability and proliferation of cancer cells, making ATR a potential therapeutic target. Here we use selective ATR inhibitors to demonstrate that acute inhibition of ATR kinase activity yields rapid cell lethality, disrupts the timing of replication initiation, slows replication elongation, and induces fork collapse. We define the mechanism of this fork collapse, which includes SLX4-dependent cleavage yielding double-strand breaks and CtIP-dependent resection generating excess single-stranded template and nascent DNA strands. Our data suggest that the DNA substrates of these nucleases are generated at least in part by the SMARCAL1 DNA translocase. Properly regulated SMARCAL1 promotes stalled fork repair and restart; however, unregulated SMARCAL1 contributes to fork collapse when ATR is inactivated in both mammalian and Xenopus systems. ATR phosphorylates SMARCAL1 on S652, thereby limiting its fork regression activities and preventing aberrant fork processing. Thus, phosphorylation of SMARCAL1 is one mechanism by which ATR prevents fork collapse, promotes the completion of DNA replication, and maintains genome integrity.